Health Literacy Among University Students in the COVID-19 Pandemic: A Systematic Review - Mohammadreza Arzaghi; Neda Tizro; Parna Ghannadikhosh; Parisa Alsadat Dadkhah; Razieh Mohammadi-Dashtaki; Saleh Behzadi; Fereshteh Sohrabivafa; Kiana Naghavi; Ali Sanaye Abbasi; Ali Darroudi; Mohammad Abbasalizadeh; Ali kheirandish; et al. (Acta Medica Indonesiana)
Background: The purpose of this systematic review was to assess different studies that worked on university students’ health literacy during covid19 pandemic and to make an overview of this issue to recognize possible determinants associated with health literacy. Methods: This review was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-analysis (PRISMA). Four databases (Google Scholar, Web of Science, Pubmed, and Scopus) were used for searching cross-sectional works that assessed the health literacy of university students. We searched papers from December 1st, 2019 up to June 10th, 2022. English language articles were used. Studies were done in countries including; Iran, Pakistan, the USA, Vietnam, China, Colombia, Germany, and Indonesia. Results: The systematic review contains 12 research studies involving 17773 students. There was a relationship between health literacy and some determinants. Positive determinants included age, female gender, Urban background, cognitive maturity, Higher educational qualification, information source (Health workers), number of semesters, and parental education. Some negative determinants were male gender, Rural background, smoking, drinking, being able to pay for medication, lower conspiracy beliefs, and higher fear of COVID-19. Conclusion: University students around the world should have courses about health literacy according to university disciplines. These courses should be available for students of different fields to enhance their effectiveness, and training should be associated with students’ needs and their subgroup traits.